Weather-based models to forecast spot blotch disease (Bipolaris sorokiniana) of wheat (Triticum aestivum) in North Bengal - CHATTOPADHAY, NIVEDITA; KUMAR, AMRENDER; MANDAL, RUPSANATAN; ROY, AYON; BHATTACHARYA, PRATEEK MADHAB; CHOWDHURY, APURBA KUMAR (The Indian Journal of Agricultural Sciences, 2021)
Experiment was laid with wheat (Triticum aestivum L.) genotypes Sonalika (susceptible check) and HD 2967 (popular variety) at Pundibari, Coochbehar, India (26o23’52”N, 89o23’26”E) on two dates of post-rainy (rabi) seasons of 2018 and 2019 at one-year interval. Data of experiments conducted previously at Pundibari were also used. Correlation values indicated that percent disease severity and Area under Disease Progress Curve on cv. Sonalika and HD 2967 had significant (P